Adverse effects of vaccines : evidence and causality - Stratton, Kathleen (National Academies Press, 2012)
"In 1900, for every 1000 babies born in the United States, 100 would die before their first birthday, often due to infectious diseases. Today, vaccines exist for many viral and bacterial diseases. The cornerstone of the vaccine safety system in the United States is the National Childhood Vaccine Injury Act. This legislation was intended to bolster vaccine research and development through federal coordination of vaccine initiatives, and by providing relief to vaccine manufacturers facing financial burdens. A key component of the legislation required the Department of Health and Human Services to collaborate with the Institute of Medicine to assess concerns about the safety of vaccines and potential adverse effects, especially in children. The Adverse Effects of Vaccines reviews the epidemiological, clinical, and biological evidence regarding adverse health effects associated with specific vaccines covered by the Vaccine Injury Compensation Program including varicella zoster vaccine, influenza vaccines, hepatitis B vaccine, and the human papillomavirus vaccine, among others. For each possible adverse event, the report reviews prior studies, summarizes their findings, and evaluates the epidemiological evidence. It finds that while no vaccine is 100% safe, very few adverse events are shown to be caused by vaccines. In addition, the evidence shows that vaccines do not cause several conditions of recent concern. For example, the MMR vaccine is not associated with autism or childhood diabetes. The DTaP vaccine is also not associated with diabetes and the influenza vaccine given as a shot does not exacerbate asthma. The Adverse Effects of Vaccines will be of special interest to the National Vaccine Program Office, the Centers for Disease Control and Prevention, vaccine safety researchers and manufacturers, parents, caregivers, and health professionals in the private and public sectors"--Publisher's description